n = 1 ∑ ∞ n H n − ln n − γ = − a γ t − h γ i + i 1 π n
The equation above holds true for positive integers t , a , h , i , n and i 1 . Find t + a + h + i + n + i 1 .
Notations :
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
My method is to find a partial sum formula. Since partial sums have finitely many terms, we can break up the sum into three parts:
(1) First let's find a formula for n = 1 ∑ m n H n . This sum expands to n = 1 ∑ m k = 1 ∑ n k 1 n 1 = k < n ≤ m ∑ k 1 n 1 + k = 1 ∑ m k 2 1 . This is close to the formula for H m 2 , which is: H m 2 = n = 1 ∑ m k = 1 ∑ m k 1 n 1 = k < n ≤ m ∑ k 1 n 1 + n < k ≤ m ∑ k 1 n 1 + k = 1 ∑ m k 2 1 = 2 ( n = 1 ∑ m n H n ) − k = 1 ∑ m k 2 1 Hence, n = 1 ∑ m n H n = 2 1 ( H m 2 + k = 1 ∑ m k 2 1 )
(2) To find the formula for n = 1 ∑ m ( − n ln ( n ) ) , we need to use the generalized Stieltjes constant: γ 1 ( m ) = r → ∞ lim [ k = m ∑ r k ln ( k ) − 2 ln 2 ( r ) ] Observe that: γ 1 ( m + 1 ) − γ 1 ( 1 ) = r → ∞ lim [ k = m + 1 ∑ r k ln ( k ) − k = 1 ∑ r k ln ( k ) ] = − k = 1 ∑ m n ln ( n ) Therefore, n = 1 ∑ m ( − n ln ( n ) ) = γ 1 ( m + 1 ) − γ 1
(3) The formula for n = 1 ∑ m ( − n γ ) is obviously − γ H m
SO, putting all of this together, we get our total partial sum formula: n = 1 ∑ m n H n − ln ( n ) − γ = 2 1 ( H m 2 + k = 1 ∑ m k 2 1 ) + γ 1 ( m + 1 ) − γ 1 − γ H m = 2 ( H m − γ ) 2 + γ 1 ( m + 1 ) − 2 γ 2 − γ 1 + 2 1 k = 1 ∑ m k 2 1
If we let m approach infinity, the last three terms give us the desired result: − 2 γ 2 − γ 1 + 1 2 π 2
All that remains is to prove that lim m → ∞ ( 2 ( H m − γ ) 2 + γ 1 ( m + 1 ) ) = 0 : m → ∞ lim ( 2 ( H m − γ ) 2 + γ 1 ( m + 1 ) ) = m → ∞ lim [ ( 2 ( H m − γ ) 2 − 2 ln 2 ( m ) ) + 2 ln 2 ( m ) + r → ∞ lim ( k = m + 1 ∑ r k ln ( k ) − 2 ln 2 ( r ) ) ] = m → ∞ lim ( 2 ( H m − γ ) 2 − 2 ln 2 ( m ) ) + m → ∞ lim ( 2 ln 2 ( m ) − k = 1 ∑ m k ln ( k ) ) + r → ∞ lim ( k = 1 ∑ r k ln ( k ) − 2 ln 2 ( r ) ) = m → ∞ lim ( 2 ( H m − γ ) 2 − 2 ln 2 ( m ) ) − γ 1 + γ 1 = 2 1 m → ∞ lim ( ( H m − γ ) 2 − ln 2 ( m ) ) Now to prove that this limit is equal to zero, we need to know that lim m → ∞ m ( H m − ln ( m ) − γ ) = 2 1 . I'll prove this at the end. 2 1 m → ∞ lim ( ( H m − γ ) 2 − ln 2 ( m ) ) = 2 1 m → ∞ lim m ( H m − ln ( m ) − γ ) ( m H m + ln ( m ) − γ ) = 2 1 ⋅ 2 1 m → ∞ lim ( m H m + ln ( m ) − γ ) We can show using the Squeeze Theorem that lim m → ∞ ( m H m + ln ( m ) − γ ) = 0 . Thus lim m → ∞ ( 2 ( H m − γ ) 2 + γ 1 ( m + 1 ) ) = 0 . □
Now, as promised, I will prove that lim m → ∞ m ( H m − ln ( m ) − γ ) = 2 1 :
m → ∞ lim m ( H m − ln ( m ) − γ ) = m → ∞ lim 1 / m ψ ( m + 1 ) − ln ( m ) The antiderivative of the numerator is ln ( Γ ( m + 1 ) ) − m ln ( m ) + m = ln ( m ! m m e m ) . By Stirling's Approximation, this is asymptotic to ln ( 2 π m ) (and therefore approaches infinity). Meanwhile, the antiderivative of the denominator is ln ( m ) which also approaches infinity. Therefore, by L'Hopital's rule (in reverse), we have: m → ∞ lim 1 / m ψ ( m + 1 ) − ln ( m ) = m → ∞ lim ln ( m ) ln ( m ! m m e m ) = m → ∞ lim lo g m ( 2 π m ) = 2 1